Historic Earthquakes for the Xianshuihe Fault Derived From Lake Mugeco in the Southeastern Margin of the Tibetan Plateau During the Past 300 Years - Liu, Liyuan; Yang, Jingxuan; Liu, Xingqi; Mao, Xin; Qin, Rong (Frontiers in Earth Science, 2022)
The lacustrine deposition with continuity and chronological reliability is one of the important archives to establish paleo-seismic sequences. In this study, sediment short cores were obtained from Lake Mugeco, located in the Selaha section of the Xianshuihe fault zone on the southeastern margin of the Tibetan Plateau. The chronology is established using 210Pb/137Cs and AMS14C dating results. Seismic events are identified based on sedimentary characteristics (color, density, and grain size), organic matter content, and high-resolution XRF element scanning data for the past 300 years. There are four whitish turbidites in the sediments of Lake Mugeco, which are characterized by a high content of clay fraction and detrital elements (K, Rb, Ca, Sr, Ti, and Si) and low organic matter content. These four turbidites were dated in 1944–1956 C.E., 1919–1932 C.E., 1673–1837 C.E., and 1507–1739 C.E., with dating errors, possibly corresponding to large historical earthquakes of 1955 (Ms 7.5), 1932 (Ms 6), 1786 (Ms 7 ¾), and 1725 (Ms 7) recorded in the Selaha section of the Xianshuihe fault zone. This study provides scientific evidence for further reconstructing longer-temporal seismic events in the Xianshuihe fault zone inferred from sediments of Lake Mugeco.